2011
DOI: 10.1126/science.1209418
|View full text |Cite
|
Sign up to set email alerts
|

Lipases in Cachexia

Abstract: Enzymes expressed in adipose tissue are involved in the loss of fat mass that occurs in a cancer-associated wasting disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 11 publications
4
45
0
2
Order By: Relevance
“…This aspect was not evident in the WSC patients. AT atrophy induced by cachexia has been consistently demonstrated in both patients7, 33 and animal models 9, 34. In CC, longitudinal investigation has suggested that fat loss is not only due to loss of adipocyte volume (lipolysis)29, 34, 35 but also may be attributed to a decrease in lipid accretion in these cells,36 both resulting in a smaller cell 37.…”
Section: Discussionmentioning
confidence: 99%
“…This aspect was not evident in the WSC patients. AT atrophy induced by cachexia has been consistently demonstrated in both patients7, 33 and animal models 9, 34. In CC, longitudinal investigation has suggested that fat loss is not only due to loss of adipocyte volume (lipolysis)29, 34, 35 but also may be attributed to a decrease in lipid accretion in these cells,36 both resulting in a smaller cell 37.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cachexia induces wasting of fat mass that accounts for a large part of the dramatic weight loss observed both in humans (Fouladiun et al 2005, Agustsson et al 2007, Dahlman et al 2010) and in animals (Machado et al 2004, Bing et al 2006, Asp et al 2010, and lipid metabolism is markedly altered (Seelaender et al 1996, Tisdale 2009, Arner 2011. Walker 256-induced cachexia was efficient at eliciting loss of body weight in terms of both absolute and relative weight (percentage of total body mass) of the fat depots, with consequent abnormalities in plasma biochemical profile.…”
Section: Discussionmentioning
confidence: 99%
“…During the development of cancer cachexia, a well-characterised loss of both adipose tissue and skeletal muscle occurs (Dahlman et al 2010, Arner 2011. It has been proposed that the former often precedes and is more rapid than the latter (Fouladiun et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is strong interaction between lipolysis and muscle wasting [66][67][68]. This may also be relevant in heart disease [69].…”
Section: Search Strategymentioning
confidence: 99%